Quranic Perspectives on the Hedonic Treadmill: An Analytical Study of Wahbah Zuhaili's Interpretation in al-Munir - Syahridho, Muhammad Fadhil; Marsuki, Muhammad Jalaluddin; Binta, Silmi Malina (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2024)
The Hedonic Treadmill phenomenon illustrates the human tendency to pursue material pleasures without achieving sustainable satisfaction. The Qur'an warns about the dangers of excessive love of the world in QS. Āli 'Imrān [3]: 14, QS. At-Takāṣur [102]: 1, and QS. Al-Fajr [89]: 20. This study aims to analyze the phenomenon through the approach of the study of mufasir figures, focusing on Wahbah Zuhaili's interpretation in Tafsir al-Munir. Qualitative-descriptive method is employed, utilizing primary data from Wahbah Zuhaili's interpretation and secondary data from literature related to Hedonic Treadmill. The analysis involves collecting relevant verses, tracing the asbabun nuzul (context of revelation), and interpreting these verses within the framework of Islamic teachings that emphasize a balance between worldly and spiritual matters, according to Zuhaili's perspective. The findings indicate that, in his view, the Qur'an critiques the tendency towards excessive materialism and encourages individuals to achieve true happiness through obedience to Allah, strengthening spirituality, and a adopting simple lifestyle.